Simplified seismic assessment of railway masonry arch bridges by limit analysis. Issue 5 (3rd May 2016) - da Porto, Francesca; Tecchio, Giovanni; Zampieri, Paolo; Modena, Claudio; Prota, Andrea
Abstract : In this work, the seismic capacity of single and multi-span masonry arch bridges was assessed by limit analysis. A preliminary statistical survey was carried out on a stock of about 750 railway bridges in Italy, classified according to characteristics and expected collapse mechanisms under seismic excitation. A comprehensive parametric study was carried out on identified homogeneous classes, to calculate limit horizontal accelerations triggering the collapse mechanism in longitudinal and transverse directions. Iso-acceleration envelope curves, representing limit horizontal acceleration of the bridge as a function of geometric parameters, were then derived. These graphs can be used for preliminary seismic safety checking of existing masonry bridges, once the main geometric parameters are available by simple visual inspections and geometric surveys, and can easily be implemented in a Bridge Management System to prioritise seismic retrofitting interventions.